Antifungal activity of the essential oil extracted from Zanthoxylum piperitum seeds against Aspergillus flavus - Chorpaka Phuangsri (2018)
© 2017, Chiang Mai University. All rights reserved. The antifungal activity of essential oil extracted from Zanthoxylum piperitum seeds was tested and the oil’s potential as a food preservative was evaluated. The main chemical components determined in the oil were β-phelladrene (23.2%), sabinene (14.6%), and brevifolin (11.9%). The oil’s antifungal activity was tested in solid and liquid cultures of aflatoxigenic Aspergillus flavus. The minimum inhibitory concentration of oil was 4.5 µL/mL. The possible actions against A. flavus are distortion in conidial heads and decrease of hyphal diameters as observed under a light microscope. A reduction in the ergosterol content in fungal plasma membrane by 34.41% also occurred. The use of this essential oil as an antifungal coat was tested on dried bird chili. The essential oil at 4.5 and 9.0 µL/mL reduced fungal development on chili peel to 45.20% and 89.32%, respectively. Thus, application as a food preservative is possible.